2017
DOI: 10.1186/s13046-017-0522-4
|View full text |Cite
|
Sign up to set email alerts
|

AHNAK suppresses tumour proliferation and invasion by targeting multiple pathways in triple-negative breast cancer

Abstract: BackgroundAHNAK, also known as desmoyokin, is a giant protein with the molecular size of approximately 700 kDa and exerts diverse functions in different types of cancer.ResultsIn the present study, we demonstrated that AHNAK mRNA levels were down-regulated in 7 out of 8 human breast cancer cell lines, especially in triple - negative breast cancer (TNBC) cell lines. Moreover, in patients with TNBC, the expression of AHNAK gene was inversely correlated with the tumor status (P = 0.015), lymph node status (P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
59
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 54 publications
3
59
0
3
Order By: Relevance
“…AHNAK was described as a nucleoprotein in neuroblastoma cell lines, where its expression was significantly suppressed (36), whereas in a study of melanoma, immunoreaction was observed mainly in the cytoplasm of normal cells, as oppose to loss of expression in melanoma cells (35). Based on these observations, the authors suggested that AHNAK may have a tumor suppressor role, which is in accord with our findings, as well as those of other studies (39,43). In our study, the levels of AHNAK protein and transcript were both significantly decreased in bladder urothelial carcinoma compared to benign urothelial lesion samples, based on proteomics and TCGA data.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…AHNAK was described as a nucleoprotein in neuroblastoma cell lines, where its expression was significantly suppressed (36), whereas in a study of melanoma, immunoreaction was observed mainly in the cytoplasm of normal cells, as oppose to loss of expression in melanoma cells (35). Based on these observations, the authors suggested that AHNAK may have a tumor suppressor role, which is in accord with our findings, as well as those of other studies (39,43). In our study, the levels of AHNAK protein and transcript were both significantly decreased in bladder urothelial carcinoma compared to benign urothelial lesion samples, based on proteomics and TCGA data.…”
Section: Discussionsupporting
confidence: 82%
“…When AHNAK was initially identified in normal bovine muzzle epidermal cells, immunofluorescent microscopy revealed a patchy staining pattern along the cytoplasmic membrane (40); however, various other cell-type-specific intracellular locations have been described in further reports (38,41). Absence of uniform expression of AHNAK has consistently been described in malignant tumors, with diverse intracellular localization depending on the type of tumor cell (38,(41)(42)(43)(44). AHNAK was described as a nucleoprotein in neuroblastoma cell lines, where its expression was significantly suppressed (36), whereas in a study of melanoma, immunoreaction was observed mainly in the cytoplasm of normal cells, as oppose to loss of expression in melanoma cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…Contudo, a maioria dos trabalhos de expressão gênica avalia somente o potencial prognóstico dos genes, enquanto uma quantidade reduzida analisa o poder preditivo de genes em amostras de neoplasias primárias e metástases de linfonodos em câncer de mama (BERTUCI et al, 2000;HUANG et al, 2003;ABBA et al, 2007;FENG et al, 2007;WANG et al, 2013;VALENTE et al, 2014;CHEN et al, 2017;PAULA et al, 2017). Além disso, o significado biológico do envolvimento dos linfonodos e sua utilidade na orientação da terapia adjuvante e sistêmica tem sido objeto de muitos resultados discordantes (BERTUCI et al, 2000;HUANG et al, 2003;ABBA et al, 2007).…”
Section: Discussionunclassified
“…Em relação à análise de expressão em genes individuais como potenciais fatores preditivos em tumores mamários, também há poucos estudos publicados na literatura (WANG et al, 2013;SHRIVER;HUEMAN;ELLSWORTH, 2014;PAULA et al, 2017;CHEN et al, 2017). Shriver, Hueman e Ellsworth (2014) detectaram a expressão diferencial dos genes DKK1, IGJ, SCGB1D2, SERPINA1, TFF1, TFF3 e TMSB15A quando compararam neoplasias malignas primárias obtidas de pacientes linfonodo negativo com neoplasias malignas primárias linfonodo positivo, sugerindo esses genes como potenciais marcadores preditivos em câncer de mama.…”
Section: Discussionunclassified
See 1 more Smart Citation